Gliding-Guided Projectile Attitude Tracking Controller Design Based on Improved Adaptive Twisting Sliding Mode Algorithm - Wenguang Zhang; Wenjun Yi (International Journal of Aerospace Engineering)
The finite-time attitude tracking control for gliding-guided projectile with unmatched and matched disturbance is investigated. An adaptive variable observer is used to provide estimation for the unmeasured state which contains unmatched disturbance. Then, an improved adaptive twisting sliding mode algorithm is proposed to compensate for the matched disturbance dynamically with better transient quality. Finally, a proof of the finite-time convergence of the closed-loop system under the disturbance observer and the adaptive twisting sliding mode-based controller is derived using the Lyapunov technique. This attitude tracking control scheme does not require any information on the bounds of uncertainties. Simulation results demonstrate that the proposed method which is able to acquire the minimum possible values of the control gains guaranteeing the finite-time convergence performs well in chattering attenuation and tracking precision.